Partai Politik Dalam Sorotan Kinerja Dan Persepsi Pemilih - Efriza, Efriza (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
This paper tries together the political parties as well as the parliamentary institution pascareformasi based on perfomance and public perception. Political parties and parliamentary bodies considered as part of the pillars of democracy are not trusted by the public. This study finds the belief of the declining public againt political actors or politicians, irony as well as paradox, pascareformasi turns out political parties that suspended cause deterioration of democracy in Indonesia